ANALISIS WACANA KRITIS TEORI INCLUSION THEO VAN LEEUWEN DALAM BERITA KRIMINAL PEMBUNUHAN BRIGADIR JOSHUA DENGAN TERSANGKA FERDY SAMBO - Iwan Kamaludin; Agus Hamdani (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2023)
This research analyzes the use of Theo Van Leeuwen's Inclusion Theory in criminal news concerning the murder of Brigadier Joshua on tvonenews.com, edition July 13, 2022. Data collection was conducted through three stages: (1) reading and understanding the discourse titled